Problems and challenges in teaching the clarinet / Norul Haslina Alias. - Alias, Norul Haslina (2011)
This study is to identify the problems of learning to play the clarinet, and also describe how to overcome the problems. It will conduct with four samples which is lecturer and teachers of clarinet. Result showed that teachers faced for the same problems, there are fingering, produce sound, breathing, and physical attributes of the clarinet player. The problems were overcome by the technique that many techniques.